Measuring price selection in microdata: It's not there - Peter Karadi; Raphael Schoenle; Jesse Wursten (European Central Bank (ECB), 2021)
We use microdata to estimate the strength of price selection - a key metric for the effect of monetary policy on the real economy. We propose a product-level proxy for mispricing and assess whether products with larger mispricing respond with a higher probability to identified monetary and credit shocks. We find that they do not, suggesting selection is absent. Instead, we detect state-dependent adjustment on the gross extensive margin. Our results are broadly consistent with second-generation state-dependent pricing models and sizable effects of monetary policy on the real economy.
Keywords: E31; E32; E52; 330; monetary non-neutrality; state-dependent pricing; identified credit and monetary policy shocks; price-gap proxy; scanner data; PPI microdata